Role of Lactate in Inflammatory Processes: Friend or Foe - Manosalva, Carolina; Quiroga, John; Hidalgo, Alejandra I.; Alarcón, Pablo; Ansoleaga, Nicolás; Hidalgo, María Angélica; Burgos, Rafael Agustín (Frontiers in Immunology, 2022)
During an inflammatory process, changes in the cellular metabolism associated with an increase in extracellular acidification are well-known features. This pH drop in the inflamed tissue is largely attributed to the presence of lactate by an increase in glycolysis. In recent years, evidence has accumulated describing the role of lactate in inflammatory processes; however, there are differences as to whether lactate can currently be considered a pro- or anti-inflammatory mediator. Herein, we review these recent advances on the pleiotropic effects of lactate on the inflammatory process. Taken together, the evidence suggests that lactate could exert differential effects depending on the metabolic status, cell type in which the effects of lactate are studied, and the pathological process analyzed. Additionally, various targets, including post-translational modifications, G-protein coupled receptor and transcription factor activation such as NF-κB and HIF-1, allow lactate to modulate signaling pathways that control the expression of cytokines, chemokines, adhesion molecules, and several enzymes associated with immune response and metabolism. Altogether, this would explain its varied effects on inflammatory processes beyond its well-known role as a waste product of metabolism.